Kānčhatkān rōk rư̄arang nai chumchon : wēthī sēwana rūam phatthanā rabop sukkhaphāp chumchon khrang thī 7, 27 Mīnākhom 2555 ʻĀkhān Sukkhaphāp hǣng Chāt Krasūang Sāthāranasuk Čhangwat Nonthaburī (Samnakngān Wičhai læ Phatthanā Rabop Sukkhaphāp Chumchon, Sathāban Phatthanā Sukkhaphāp ʻĀsīan, Mahāwitthayālai Mahidon, 2012)
Collected articles on the government policies and the management of chronic diseases in all communities of Thailand; proceedings of the 7th forum on participatory action for the development of community-based health care service system in the country.